2022
DOI: 10.7717/peerj.14334
|View full text |Cite
|
Sign up to set email alerts
|

The biological function of m6A methyltransferase KIAA1429 and its role in human disease

Abstract: KIAA1429 is a major m6A methyltransferase, which plays important biological and pharmacological roles in both human cancer or non-cancer diseases. KIAA1429 produce a tumorigenic role in various cancers through regulating DAPK3, ID2, GATA3, SMC1A, CDK1, SIRT1 and other targets, promoting cell proliferation, migration, invasion, metastasis and tumor growth . At the same time, KIAA1429 is also effective in non-tumor diseases, such as reproductive system and cardiovascular system diseases. The potential regulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…Our findings demonstrated that KIAA1429 contributed to OSCC tumorigenesis by inducing m6A methylation of INHBA in OSCC cell lines. KIAA1429, an m6A methyltransferase, plays a tumorigenic role in multiple cancers by mediating m6A modification of mRNA, lncRNA, and circRNA 21 . KIAA1429 is upregulated and plays an oncogenic role in both breast and gastric cancer 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings demonstrated that KIAA1429 contributed to OSCC tumorigenesis by inducing m6A methylation of INHBA in OSCC cell lines. KIAA1429, an m6A methyltransferase, plays a tumorigenic role in multiple cancers by mediating m6A modification of mRNA, lncRNA, and circRNA 21 . KIAA1429 is upregulated and plays an oncogenic role in both breast and gastric cancer 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…VIRMA has been primarily investigated in the context of cancer and has been reported as an oncogenic factor in various cancer types, including breast cancer 18,19 . However, the specific molecular mechanisms underlying its oncogenic role vary significantly, involving both m 6 A-dependent and m 6 A-independent pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The m6A writer complex includes the catalytic methyltransferase like 3 (METTL3) which forms a stable complex with methyltransferase like 14 (METTL14) forming the m6A-METTL Complex (MAC) in which METTL3 transfer the methyl group from S-adenosyl methionine (SAM) to the adenosine residue within the RRACH consensus motif in RNA [ 62 , 63 ]. In addition to the MAC, the m6A writer complex includes regulatory subunits, i.e., Wilms’ tumor 1 (WT1)-associating protein (WTAP) [ 64 ], Vir like m6A methyltransferase associated (VIRMA) [ 65 , 66 , 67 ], RNA binding motif protein 15 (RBM15) [ 68 ], RNA binding motif protein 15B (RBM15B) [ 68 , 69 ], and zinc finger CCCH-type containing 13 (ZC3H13) [ 70 ]. These proteins interact with MAC and modulate its activity and/or target specificity [ 71 , 72 , 73 ].…”
Section: N6-methyladenosine (M6a)mentioning
confidence: 99%